The Freemasonry in the Island Space of Portuguese Atlantic: The Catholic origins of Madeiran Freemasonry - Santos, Fernanda Cristina (2018)
Centuries of controversy, prohibitions and mutual attacks have made Freemasonry and the Catholic Church somewhat irreconcilable adversaries. Nonetheless, the attraction Freemasonry has had for members of the Church in its origins is still paradoxical and continues nowadays. In the ranks of Freemasonry, and particularly in the Masonic leaderships, there were members from the Catholic Church, especially from its secular and regular clergy. If this was true at an international level, it was even more so in catholic countries where masonic obedience was eloquently implemented, especially in our case study, which is the archipelago of Madeira. How can we explain this attraction and this crossing of forbidden frontiers, especially of Catholics who joined Freemasonry, while continuing their catholic practice? Throughout this study we will try to understand Freemasonry as a movement and an institution, in latu sensu, that sought to constitute elites of high intellect and social influence.